The Whiplash Disease Reconsidered - Astrup, Jens; Gyntelberg, Finn (Frontiers in Neurology, 2022)
The natural course of the whiplash disease is reconsidered in relation to the predominant view of its cause. It is assumed that a whiplash type trauma is causing an acute tissue injury such as a distortion or sprain in the neck followed by neck pain and headache which then tends to become a chronic pain condition. We conclude that the whiplash disease typically evolves following a minor trauma without any signs of a tissue injury. It presents with central neuromotor dysfunction such as EMG hyperactivity and abnormal activation patterns associated with dyscoordination of the involved and adjacent muscle groups. This indicates a central neurological rather than a peripheral traumatic pathology. This view places the cause of the whiplash disease within the central nervous system, and in concordance with the EMG abnormalities and motor dyscoordination we suggest the term cervical spinal dyssynergia for this pathology. It provides a new paradigm for further investigations of this disease as well as a window for possible specific neuropharmacological therapy directed towards the dysfunctional neuromotor control.